(untitled) (Journal of Dhaka Medical College, 2024)
Background: Carcinoma larynx is one of the most common cancers in the head neck region. Mortality and morbidity in this disease is still high in spite of modern treatment modalities. Smoking and Alcohol is recognized as common predisposing factor for carcinoma larynx. Neck node metastasis increases the mortality twice than the primary alone. Most of the Laryngeal carcinoma patient with neck node metastasis are smoker in our country. Stopping the consumption of tobacco may reduce both mortality and morbidity of carcinoma larynx. Metastasis is more common in supra-glottic carcinoma of larynx. This study is carried to observe the association of tobacco with lymph node metastasis in supra-glottic carcinoma of larynx. Materials and Methods: This cross sectional study was conducted in Otolaryngology and head Neck surgery department of Dhaka Medical College and Mitford Hospital of Dhaka, Bangladesh from June 2013 to June2015 .212 cases of supra-glottic carcinoma age ranging from 35 year to 90 years (mean age 63.6 ±11.65) was included in this study. Results: Sixty two percent patients were diagnosed with cervical lymph node metastasis. 83.28% patients with nodal metastasis were above 60 years of age and 75.67% patients were manual worker.100% node positive patients were smoker. Smoking for longer period (>30yrs) and higher in number (>30 sticks/day) were found in advanced stage. Significant association was found between site, size, macroscopic features, cellular differentiation and demographic factors of patient with neck node metastasis in supra-glottic carcinoma larynx. Conclusion: As neck node metastasis significantly reduces prognosis so we must be more attentive towards factors that increase the chance of nodal metastasis to avoid the advancement of the disease. J Dhaka Med Coll. 2023; 32(1) : 51-56